Clinical, Laboratory, Radiological, Bronchoscopic, and Outcome Characteristics of Pulmonary Fungal Infection in Children in PICU in Central China: A Case Series - Huang, Chengjiao; Xiao, Shuna; Cheng, Yin; Li, Yong; Xia, Zhi; Tang, Wen; Shi, Buyun; Qin, Chenguang; Xu, Hui; Shu, Xiaolan (Frontiers in Pediatrics, 2022)
Objective: Fungal infections are common in pediatric intensive care units (PICUs), but the monitoring methods are limited. This study analyzed the differences in clinical features, diagnosis, and treatment between PICU patients with and without fungal infection. Methods: This retrospective study analyzed PICU patients at the Maternal and Child Health Hospital of Hubei Province diagnosed with severe pneumonia between January 2015 and January 2020. The patients were divided into the fungal (F) and non-fungal (NF) infection groups. Levels of 1,3-beta-D-glucan (BDG) and galactomannan (GM) in serum and bronchoalveolar lavage fluid (BALF) were analyzed. Chest computed tomography (CT) images were reviewed. Results: A total of 357 patients were included. In the F group, fever, moist rales, coarse rales, shortness of breath, and sepsis were more common (all P<0.05); PICU time, hospitalization duration, and BDG- and GM-positive rates in serum and BALF were all significantly higher than in the NF group (all P<0.05). The BDG- and GM-positive rates in serum and BALF were higher in the F than in the NF group (all P<0.05). The abnormal lymphocyte ratios in serum were higher in the F group (all P<0.05). Wedge-shaped, patchy, streaky shadows and subpleural reticulation were higher in CT images of the F group (all P<0.05). Tracheobronchial stenosis was more common in pulmonary fibroscopy results of the F group (P=0.04). Conclusion: PICU pneumonia patients with fungal infection have specific clinical and laboratory features compared with those without fungal infection, including higher rates of BALF, serum BDG, GM positivity and tracheobronchial stenosis.